Effect of Human Activities and Seasonal Variation on Water Quality of Nkenye (Chikuu) Stream in Chuka, Kenya - Ombaka, O.; Gichumbi, J.M.; Mukono, Simon K.; Kibara, D. (My University, 2013)
Composite water and sediment samples were taken from Nkenye stream at five different sampling stations during wet and dry seasons. Water quality parameters were analyzed using standard methods to ascertain the effect of human activities on the water quality. The variations in the physicochemical and biological parameters were observed from station to station both in the dry and wet seasons. These variations were attributed to human activities. Results showed significant seasonal variation in most measured parameters with a few showing significant spatial variation. The characteristics of the water from the stream revealed an acceptable quality for most of measured parameters when compared with drinking water standards. However, high values of turbidity, iron, manganese, chromium and microbial load were recorded compared with drinking water standards, which call for proper treatment of the water before being used by the public. The results of sediment samples revealed that silicate, iron, aluminum are present in major quantities while other minerals are present in trace amounts. Thus the present study concludes that Nkenye stream water is contaminated and needs attention for it to be safe for domestic use.
Keywords: total coliforms; microbial parameters; total dissolved solids; electrical conductivity; alkalinity; hardness